ETIKA JUAL BELI ONLINE DALAM ISLAM - Muhammad Ali, Zulkarnain (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2022)
Technological developments have changed the way people make buying and selling transactions. In the digital era, people prefer to buy and sell online, because it is more efficient and effective. can be done anywhere. However, this creates a variety of new problems such as opportunities to commit fraud, inappropriate payments and delivery of goods, unsecured guarantees, which ultimately result in losses to one party or both parties. This study aims to determine ethics in the implementation of online buying and selling according to Islam. The author uses qualitative research methods with library research methods. The results of the study indicate that the ethics of buying and selling online must prioritize the values ​​contained in the Qur'an and hadith. These values ​​include unity, balance, free will, responsibility, truth, virtue and honesty. The purpose of applying ethics in online buying and selling is to protect the benefit of individuals, property and the state. It is also a form of respect for every soul. By applying Islamic ethics in buying and selling, a healthy and blessed business climate will be achieved so that an Islamic society structure can be achieved. The first ethics of buying and selling online is not buying and selling in vanity that brings injustice to others such as usury, gambling, ghasab (stealing), treason, dishonesty, cheating, committing perjury, hoarding goods, monopoly, while selling ethics the second online buying is to please each other by being friendly, not criticizing other people's business. With the application of these two buying and selling ethics, benefits will be achieved in life both individually, in society, and in the state.